Genome and classification of viruses (British Journal of Multidisciplinary and Advanced Studies, 2023)
The types of classification of viruses available in literature include ICTV Classification, Holmes Classification, LHT System of Virus Classification, Casjens & Kings Classification of Virus, and Baltimore Classification of Virus. Out of the aforementioned schemes of classification Baltimore classification of viruses which classified viruses into seven groups was found to be more pragmatic than others being free from bewildering events. Baltimore classification of viruses placed mRNA in the center, and described the obligatory pathways to mRNA from DNA or RNA Genomes. It is an obligatory relationship between the viral Genome & its mRNA. The key objective of this study is to forward a pragmatically consistent and persuasive scheme for the classification of viruses where the Genome is the unit of both structure & function of every individual of viruses and of all other genomic-things.